Kecerdasan Emosional dan Burnout di Sektor Perbankan: Peran Mediasi Self-Efficacy - Putra, Al Ikhlas; Andriani, Chichi (Jurnal Informatika Ekonomi Bisnis, 2025)
This study aims to analyze and examine the effect of Emotional Intelligence on Burnout, the effect of Self-Efficacy on Burnout, and the mediating role of Self-Efficacy in the relationship between Emotional Intelligence and Burnout among employees of PT Bank Nagari Head Office, West Sumatra. Employing a descriptive-causative approach, the research involved a population comprising all head office employees, with a sample of 161 respondents selected using cluster proportional random sampling. Data were collected through a questionnaire utilizing a Likert scale and analyzed using Structural Equation Modeling with SmartPLS 4. The findings reveal that Emotional Intelligence has a negative and significant effect on Burnout, and Self-Efficacy also exerts a negative and significant effect on Burnout. Furthermore, Self-Efficacy significantly mediates the relationship between Emotional Intelligence and Burnout. These results indicate that higher levels of emotional intelligence and self-efficacy among employees are associated with a lower tendency to experience burnout in the workplace.